Securing Property Rights In Transition : Lessons From Implementation of China's Rural Land Contracting Law - Deininger, Klaus W., 1962- 1962- (The World Bank, 2008)
This paper is motivated by the emphasis on secure property rights as a determinant of economic development in recent literature. The authors use village and household level information from about 800 villages throughout China to explore whether legal reform increased protection of land rights against unauthorized reallocation or expropriation with below-average compensation by the state. The analysis provides nation-wide evidence on a sensitive topic. The authors find positive impacts, equivalent to increasing land values by 30 percent, of reform even in the short term. Reform originated in villages where democratic election of leaders ensured a minimum level of accountability, pointing toward complementarity between good governance and legal reform. The paper explores the implications for situations where individuals and groups hold overlapping rights to land